The relationship between fighting style, cognition, and regional brain volume in professional combatants - Stephen, S. J.; Shan, G.; Banks, S. J.; Bernick, C.; Bennett, L. L. (Journal of Head Trauma Rehabilitation, 2020)
Objective: Repetitive head impacts (RHIs) in combat sports are associated with cognitive decline and brain volume reduction. While fighting style differences between boxers, mixed martial artists (MMAs), and martial artists (MAs) have resulted in a broader spectrum of injury, the effects of RHIs on MAs relative to other fighters have not yet been explored. This study aimed to determine a differential effect of fighting style on cognition and brain.